Students’ Perception for Online Lectures Quality in Universities in Yogyakarta - Astri Wulandari (Jurnal Pekommas, 2021)
The World of Education during the Covid-19 outbreak had to take a solution or problem solving by carrying out Teaching and Learning Activities online. Schools, campuses and even informal education facilities must go on online as a security solution while continuing to carry out learning activities in the midst of this epidemic. This study looks at the extent to which students’ assessments of the quality of online lectures in Yogyakarta. 100 students as respondents from 14 Universities in Yogyakarta participated in this survey. This study uses a quantitative method with reference to, quality assessment in the 2019 SPADA Learning Object Development Guide from the Directorate General of Learning and Students Affairs, Kemristekdikti, 2019. From the results of the study, it was found that the learning plan indicator had the highest average percentage of items is 35,5%, then the media and technology indicators have the highest percentage of items at 37,63% and the assessment and evaluation indicators have an average percentage of items is 45% which all the percentage indicators are on a pretty good rating scale. This shows that the student’s assessment of the quality of online lectures in Yogyakarta during the Covid-19 outbreak was quite goods in its implementation.